IMPLEMENTASI PENDIDIKAN BUDAYA DAN KARAKTER BANGSA DALAM BUDAYA SEKOLAH - Rochmad Dwi Susanto; Nurul Zuriah; Mohamad Syahri (University of Muhammadiyah Malang, 2017)
Education and culture to be very fundamental national character is created and maintained for the values of good character , namely : value , religious , honest , tolerance , discipline , hard work , creative, independent , democratic , curiosity , the spirit of nationalism , patriotism , appreciate the achievements , friends / communicative , love peace , love reading , environmental care , social care and responsibility . This research was conducted at SMP Negeri 3 Malang , with the aim of : ( 1 ) To describe the implementation of National Character Education Culture And Culture In Schools